DEVELOPMENT OF TRANSMYOCARDIAL LASER REVASCULARIZATION IN PATIENTS WITH ISCHEMIC HEART DISEASE - V. M. Shipulin; S. L. Andreev; I. V. Sukhodolo; E. P. Gordov; V. E. Babokin (Alʹmanah Kliničeskoj Mediciny, 2016)
The use of laser radiation in cardiac surgery allows to provide more effective and targeted care for patients with ischemic heart disease. The article summarizes the multistage teamwork of several research centers in Tomsk on determination of the most effective type of laser and techniques of cardiac surgery using lasers. The study had an experimental and a clinical phase. In the experimental phase, effectiveness of various laser types for indirect laser myocardial revascularization was assessed, including carbon dioxide, neodymium, and a semiconductor laser types. During clinical phase, efficacy of clinical use of semiconductor laser in various timepoints after surgery was evaluated. The experimental phase revealed that semiconductor laser provides the best neoangiogenesis efficiency, minimal myocardial damage and ease of use. During clinical phase, its safety for a patient was established and a significant clinical benefit was observed.